Oxide bipolar electronics: materials, devices and circuits. (20th April 2016) - Grundmann, Marius; Klüpfel, Fabian; Karsthof, Robert; Schlupp, Peter; Schein, Friedrich-Leonhard; Splith, Daniel; Yang, Chang; Bitter, Sofie; von Wenckstern, Holger
Abstract: We present the history of, and the latest progress in, the field of bipolar oxide thin film devices. As such we consider primarily pn-junctions in which at least one of the materials is a metal oxide semiconductor. A wide range of n-type and p-type oxides has been explored for the formation of such bipolar diodes. Since most oxide semiconductors are unipolar, challenges and opportunities exist with regard to the formation of heterojunction diodes and band lineups. Recently, various approaches have led to devices with high rectification, namely p-type ZnCo2 O4 and NiO on n-type ZnO and amorphous zinc-tin-oxide. Subsequent bipolar devices and applications such as photodetectors, solar cells, junction field-effect transistors and integrated circuits like inverters and ring oscillators are discussed. The tremendous progress shows that bipolar oxide electronics has evolved from the exploration of various materials and heterostructures to the demonstration of functioning integrated circuits. Therefore a viable, facile and high performance technology is ready for further exploitation and performance optimization.